Being from a Bad Neighbourhood: Confronting Bad Decision Discourses in the Impoverished Inner City - Bisaillon, Laura; Hassan, Mehdia; Hassan, Maryam (Imaginations)

(untitled) (York University, 2019)
This article confronts mainstream discourses about poverty and inner city poor neighbourhoods. It argues that the ways that poverty and poor inner city neighbourhoods are made publicly known in writing and through visual representations present problems such as overpowering structural causes of health and illness, reifying false dichotomy of us and them, and normalizing people living in poverty or working poor people as de facto vulnerable. This can happen when the social relations that govern poverty and sustain human suffering eschew the social relations that produce these experiences. Taking these relations as the objects of analysis, this article focuses sociologically on the Dundas/Sherbourne neighbourhood in Toronto, Canada, as the terrain of inquiry. The aim here is to contribute to analyses of the political, social, and economic determinants of health as well as to critiques of bad-neighbourhood and bad decision discourses. To do this, it bridges visual practice with critical social analysis: drawing together the authors’ individual practices as visual artists, marshaling their social positions as residents of the adjacent St. James Town neighbourhood, and sharing their experiences of the Dundas/Sherbourne area. They employ insights from sensory ethnography and street photography to offer an alternative source of knowledge about the poor inner city that contrasts and contests mainstream ways of knowing these same spaces.